Geomorphology of Inglefield Land, North Greenland. - Nichols, Robert L. (Meddelelser om Grønland, 1969)
The coastal cliffs, structural terraces, and bedrock valleys of Inglefield Land resulted from the uplift and fluvial dissection of a late Tertiary peneplain. The straits and channels between Ellesmere Island and North Greenland may be due to the submergence of this dissected peneplain by the weight of the existing Greenland ice cap. Inglefield Land was completely glaciated and the Carey Øer, 70 miles offshore from Thule, were covered by the Greenland Indlandsis, proving that during the Wisconsin the straits and channels between Ellesmere Island and Greenland were nearly or completely filled with glacial ice. C-14 measurements indicate that the deglaciation of the coastal areas near Rensselaer Bugt occurred before 8200 ± 300 B.P., and near Dallas Bugt before 6180 ± 200 B.P. Elevated deltas and beaches show that the marine limit is approximately 285 feet above sea level near Force Bugt and 210 feet at Dallas Bugt, 70 miles to the northeast. The marine terraces reported by B0GGILD at 1050-1800 feet above sea level between 77-81 degrees do not exist, and the post-Wisconsin epeirogenic movement postulated by DALY to account for them did not take place. Permafrost, solifluction, block fields, nivation cirques, earth hummocks, nonsorted circles and polygons, and ice-wedge and sand-wedge furrows are common. Although small dunes, loess, ventifacts, and wind-eroded earth hummocks are present, the work of wind is of minor importance. Surface efflorescences, travertine on the bottoms of fragments, solution-faceted and solution-shaped fragments, deposition of travertine from ponds and streams, and meteorologic data all prove that the climate has been arid for thousands of years.